2014
DOI: 10.1039/c3sm52618f
|View full text |Cite
|
Sign up to set email alerts
|

Force spectroscopy of polymer desorption: theory and molecular dynamics simulations

Abstract: Forced detachment of a single polymer chain, strongly adsorbed on a solid substrate, is investigated by two complementary methods: a coarse-grained analytical dynamical model, based on the Onsager stochastic equation, and Molecular Dynamics (MD) simulations with a Langevin thermostat. The suggested approach makes it possible to go beyond the limitations of the conventional Bell-Evans model. We observe a series of characteristic force spikes when the pulling force is measured against the cantilever displacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…where the variances σ 2 1 (Z) and σ 2 2 (Z) are evaluated at the most probable valuen according to Eqs. (6,7). From C(t) we can calculate the average relaxation time [33], τ = ∞ 0 dt C(t), giving…”
Section: Dynamic Relation and Critical Slowdownmentioning
confidence: 99%
“…where the variances σ 2 1 (Z) and σ 2 2 (Z) are evaluated at the most probable valuen according to Eqs. (6,7). From C(t) we can calculate the average relaxation time [33], τ = ∞ 0 dt C(t), giving…”
Section: Dynamic Relation and Critical Slowdownmentioning
confidence: 99%
“…Recently Paturej et al [22] study the desorption of a polymer adsorbed on an attractive wall by pulling with an external force at one end of the polymer. They have used the FJC model to describe the polymer.…”
Section: Model and Resultsmentioning
confidence: 99%
“…Force-extension isotherms were obtained in the simulations and showed that regions exist in which the molecule is mechanically unstable, which leads to unfolding and results in transitions between high-F and low-F regimes. The development of these mechanically unstable regions and the transitions between force regimes were found to be related to fluctuations in F, which in turn are related to the stiffness of the harmonic potential used to apply F. Additional simulations by Vilgis and coworkers have modeled F-induced polymer chain scission using similar models [74][75][76][77].…”
Section: Application Of F Via Artificial External Groupsmentioning
confidence: 94%